Urine cytology as a screening test for bladder infiltration in cervical cancer. Issue 4 (1st July 2006) - Snyman, L. C.; Zondagh, B. A.; Dreyer, G.; Lindeque, B. G.; Louw, M.
Abstract : Ultrasound is currently used as a screening test for bladder infiltration in patients with advanced-stage cervical cancer at our institution. Cystoscopy is reserved for patients with abnormal bladder ultrasound findings. This study was undertaken to reevaluate this policy and to compare the results of different screening tests. The study was carried out in Pretoria academic complex. All newly diagnosed cervical carcinoma patients stage II and above were included in this study. The standard staging investigations were done on all patients. In addition, urine midstream and catheter specimens were sent for cytology. Cystoscopy and biopsy were performed on all patients. Two hundred twenty-eight patients were enrolled into this study. At cystoscopy, 47 patients had bladder mucosa suspicious of malignant infiltration, of which 17 had bladder mucosa infiltration diagnosed on histology. Urine catheter cytology has a sensitivity of 94% and specificity of 82% for bladder mucosa infiltration. The predictive value of a positive test is 31% and for a negative test is 99%. Catheter urine cytology is a very useful screening test for bladder infiltration in patients with cervical cancer. Cystoscopy should be reserved for patients with abnormal urine cytology in resource-poor settings with a large burden of disease.